1994
DOI: 10.1038/sc.1994.67
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal effects of an electrical stimulation induced cycling programme in the spinal injured

Abstract: Twelve patients were involved in a 3 month stimulation induced cycling programme at the Royal Perth Rehabilitation Hospital. A number of the patients were less than 1 year post injury, all except one had an incomplete injury, and most were receiving physiotherapy. All patients who completed the programme increased their time of cycling and, in all but one case, the exercise load, indicative of a local training effect. Significant improvements were found in voluntary isometric strength, stimulated isometric str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 11 publications
5
38
0
2
Order By: Relevance
“…27,38 ± 41 After 3 months with the same amount of training as in the present study Sloan et al 40 found an increase of 9% in the quadriceps, whereas no change was seen in the hamstrings. Block et al 39 found a signi®cant increase in cross sectional area of the anterior muscle group of the thigh after 6 weeks of training whereas Bremner et al 41 found no change and explained this by a small sample size.…”
Section: Thigh Girthsupporting
confidence: 59%
“…27,38 ± 41 After 3 months with the same amount of training as in the present study Sloan et al 40 found an increase of 9% in the quadriceps, whereas no change was seen in the hamstrings. Block et al 39 found a signi®cant increase in cross sectional area of the anterior muscle group of the thigh after 6 weeks of training whereas Bremner et al 41 found no change and explained this by a small sample size.…”
Section: Thigh Girthsupporting
confidence: 59%
“…All were classified as level 4 or 5, with the exception of one level 2 trial. Training programs involving BWSTT, 32,34,35 FES cycling, 30,31,[36][37][38] FES ambulation, 39,40 neuromuscular electrical stimulation resistance training 41 and vibration exercise 42 produced significant increases in muscle mass, with training frequencies ranging from 2-7 Â per week, for 8-52 weeks duration. Of note, the level 2 trial showed significant increases in quadriceps muscle mass after 26 weeks of FES-assisted treadmill training, 2 times per week for 20 min per session.…”
Section: Standingmentioning
confidence: 99%
“…27 The expected favorable effect of FES has nevertheless not been confirmed by most 3-12-month FES programs, whether or not they were associated with cycling or assisted walking. 22,26,66,[77][78][79][80] Rodgers et al 78 used electrical stimulation of the quadriceps muscles in a knee extension exercise and reported that the bone density at the tibia remained unchanged despite improved muscle performance. The differences in training program characteristics (session frequency, training duration, and intensity) might explain these inconsistent findings.…”
Section: Physical Exercisementioning
confidence: 99%